MENYOAL INTERNET SEBAGAI RUANG PUBLIK DALAM PERSPEKTIF HABERMAS - Haezer, Eben (Institut Agama Islam Syarifuddin Lumajang, 2018)
The idea of the internet as an ideal public sphere has still become a debate. In some studies, some experts criticize the idea, but some accept it. This article discusses the problem as seen from the perspective of the theory of Public Sphere which was initiated by Jurgen Habermas It also briefly explains the thinking concept of Habermas, Virtual Public Sphere, Democracy in the Internet Age, and Visual Culture.